Probing connections between deep earth and surface processes in a land-locked ocean basin transformed into a giant saline basin: The Mediterranean GOLD project#. (September 2015) - Rabineau, M.; Cloetingh, S.; Kuroda, J.; Aslanian, D.; Droxler, A.; Gorini, C.; Garcia-Castellanos, D.; Moscariello, A.; Burov, E.; Sierro, F.; Lirer, F.; Roure, F.; et al.
Abstract: During the last decade, the interaction of deep processes in the lithosphere and mantle with surface processes (erosion, climate, sea-level, subsidence, glacio-isostatic readjustment) has been the subject of heated discussion. The use of a multidisciplinary approach linking geology, geophysics, geodesy, modelling, and geotechnology has led to the awareness of coupled deep and surface processes. Deep earth dynamics (topography, erosion, tectonics) are strongly connected to natural hazards such as earthquakes, landslides, and tsunamis; sedimentary mass transfers have important consequences on isostatic movements and on georesources, geothermal energy repartitions. The ability to read and understand the link between deep Earth dynamics and surface processes has therefore important societal impacts. Ground-truthing at carefully-selected sites of investigation is imperative to better understand these connections. Due to its youth (<30 Ma) and its subsidence history, the almost land-locked Gulf of Lion–Sardinia continental margins system provides a unique record of sedimentary deposition from the Miocene to present. Due to its high subsidence rate, palaeoclimatic variations, tectonic events and vertical evolution are all recorded here at very high resolution. The late Miocene isolation and desiccation of the Mediterranean, the youngest and most catastrophic event, the Messinian Salinity Crisis (MSC), induced drastic changes in marine environments: widespread deposition of evaporite (gypsum, anhydrite and halite) in the central basin, and intense subaerial erosion along its periphery. These extraordinary mass transfers from land to sea induced strong isostatic re-adjustments that are archived in the sedimentary record and represent a window to the lithospheric rheology and the deep processes. The GOLD (Gulf of Lion Drilling) project, proposes to explore this unique sedimentary record as well as the nature of the deep crustal structure, providing valuable information about the mechanisms underlying vertical motions in basins and their margins. Graphical abstract: Highlights: Characterization of the thermal, petrophysical and mechanical properties of the crust. Focus on the palaeoenvironment, palaeobathymetry, chronology of early Miocene sedimentation to lower Pliocene. Quantification of the consequences of the Messinian event with Thermo-mechanical models. History of water exchange between the Mediterranean Sea and the North Atlantic. Limits of life.